An Investigation of Electromyographic Activity of Trapezius and Serratus Anterior Muscles in Individuals with Scapular Dyskinesis during Different Types of Push-ups: A Systematic Review and Meta-Analysis - Ramin Arghadeh; Hooman Minoonejad; Mohammad Hosein Alizadeh; Rahman Sheikhhoseini; Parisa Sayyadi (Shiraz University of Medical Sciences, 2023)
Background:The use of push-ups has been suggested to strengthen the scapular stabilizers, while incorporating unstable surfaces is recommended to enhance the involvement of the neuromuscular system. However, the impact of this instability on electromyography (EMG) activity in the periscapular muscles during push-ups in individuals with Scapular dyskinesis remains uncertain. Consequently, the objective of the current study was to assess the influence of unstable surfaces on EMG activity in the trapezius and Serratus anterior muscles among individuals with scapular dyskinesis during push-ups.Methods:A comprehensive search was conducted in Web of Science, PubMed, and Scopus databases, covering articles published from the inception of these databases until September 25, 2021. The search strategy utilized three main keyword categories: Scapular dyskinesis, electromyography, and push-up. Initially, 5,249 articles were identified through this search process. After a thorough assessment of the full text of these articles, four studies were deemed suitable for inclusion in the final review. Data extraction and evaluation of methodological quality were carried out as part of the review process. The Standardized Mean Difference (SMD) and corresponding 95% Confidence Interval (CI) were calculated to perform the meta-analysis using Comprehensive Meta-Analysis (CMA) Software, Version 3. Statistical significance was determined by a p-value less than 0.05.Results:The findings of the study revealed that the utilization of unstable surfaces among individuals with scapular dyskinesis led to an increase in the activity of the upper trapezius (P= 0.011; SMD= 0.807 [95%CI 0.188, 1.427]). Conversely, it reduced the Serratus anterior's activity (P= 0.000; SMD= -0.665 [95%CI -1.023, -0.307]). However, the electromyography activity of the Lower trapezius was not significantly affected (P= 0.176).Conclusion:Due to the imbalance between the upper trapezius and serratus anterior muscles in individuals with scapular dyskinesis, caution should be exercised when using unstable surfaces. Incorrect utilization of unstable surfaces may worsen these individuals' muscle imbalance. Therefore, it is advisable to approach unstable surfaces with heightened caution in individuals with scapular dyskinesis.